Ring‐Opening Copolymerization of Maleic Anhydride with Functional Epoxides: Poly(propylene fumarate) Analogues Capable of Post‐Polymerization Modification. (27th August 2018) - Chen, Yusheng; Wilson, James A.; Petersen, Shannon R.; Luong, Derek; Sallam, Sahar; Mao, Jialin; Wesdemiotis, Chrys; Becker, Matthew L.
Abstract: Three functional epoxides were copolymerized with maleic anhydride to yield degradable poly(propylene fumarate) analogues. The polymers were modified post‐polymerization and post‐printing with either click‐type addition reactions or UV deprotection to either attach bioactive species or increase the hydrophilicity. Successful dye attachment, induced wettability, and improved cell spreading show the viability of these analogues in biomaterials applications.